2018
DOI: 10.1101/383042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrete or indiscrete? Redefining the colour polymorphism of the land snailCepaea nemoralis

Abstract: 6Running head: Redefining a snail colour polymorphism 7 2 Biologists have long tried to describe and name the different phenotypes that make 8 up the exuberant colour polymorphism of the land snail Cepaea nemoralis. 9 Traditionally, the view is that the ground colour is one of a few major colour classes, 10 either yellow, pink or brown, but in practise it is frequently difficult to distinguish the 11 colours, and consistently define different shades of the same colour. To understand 12 whether colour variat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…It has a long history as a model in evolutionary biology, due to its conspicuous shell polymorphism (reviewed by Jones et al, 1977; Ożgo, 2009)(Figure 1A‐B). Genetic variation in shell background color (from pale yellow to brown, but usually divided in yellow, pink, and brown; Davison et al, 2019) and in the number or width of dark bands has been well described (Jones et al, 1977). Shell polymorphism is governed by a limited number of loci with a limited number of alleles (Richards et al, 2013), and by all evidence shows no phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…It has a long history as a model in evolutionary biology, due to its conspicuous shell polymorphism (reviewed by Jones et al, 1977; Ożgo, 2009)(Figure 1A‐B). Genetic variation in shell background color (from pale yellow to brown, but usually divided in yellow, pink, and brown; Davison et al, 2019) and in the number or width of dark bands has been well described (Jones et al, 1977). Shell polymorphism is governed by a limited number of loci with a limited number of alleles (Richards et al, 2013), and by all evidence shows no phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that colour variation is multimodal but continuously variable in natural populations, necessitating the use of quantitative methods to measure it (Davison et al 2018). However, in simple crosses it is straightforward to bin the individuals into one of two types; quantitative measures are not necessary.…”
Section: Methodsmentioning
confidence: 99%
“…The ground color of adult snail shells from Vielha and Jueu valley was measured using an Ocean Optics spectrometer (model USB2000 + UV-VIS-ES) and a Xenon light source (DT-MINI-2-GS UV-VIS-NIR), as described previously (Davison et al, 2019). Briefly, the shell underside was used because it is generally unbanded and the least damaged/ F I G U R E 2 Overview of sampling locations in the Pyrenees, including this work, and previous work by others in the 1960s (Arnold, 1968;Cameron et al, 1973) exposed to sunlight, holding the probe at a 45° incident angle, ~2 mm from the shell.…”
Section: Quantification Of Shell Colormentioning
confidence: 99%
“…In practise, it is frequently difficult to distinguish the colors, and define different shades of the same color. Therefore, to understand whether color variation is in reality continuous, and to investigate how the variation may be perceived by an avian predator, psychophysical models of color vision were applied to shell reflectance measures, finding that both achromatic and chromatic variation are continuously distributed over many perceptual units in indiscrete in Cepaea nemoralis (Davison et al, 2019). Nonetheless, clustering analysis based on the density of the distribution did reveal three groups, roughly corresponding to human-perceived yellow, pink, and brown shells.…”
mentioning
confidence: 99%